Blockchain Enabled Platforms for the Internet of Things - Almeida, João Pedro Guita de (2019)
The Blockchain and the Internet of Things (IoT) have gained a lot of attention in the last few years, since both technologies enable the possibility of creating a more connected and independent world. This combination enables the design of computing systems and cyber-physical environments without the need of centralized trusted entities, giving users the freedom and control of their operations, in a decentralized ledger model. By using storing and logging mechanisms supported by the Blockchain, data is immutable and independently audited, guaranteeing that it is neither modified nor deleted. At the same time, applications can benefit from the reliability and fault-tolerance assumptions provided by the Blockchain in supporting transactions between users and involved devices. In this thesis, it was studied and proposed a generic solution for a Blockchain-enabled IoT software architecture. The proposed solution enables the advantages of using decentralized logging and ledgering, without the interference of central authorities, inherently supported by the base Blockchain reliability, availability and security foundations. These capabilities are envisaged as key-benefits for a new generation of clean-slate approaches for IoT applications with the required scalability criteria. The research conducted in the dissertation work, studied the base software foundations, relevant components and implementation options that enable the identified advantages of using Blockchain components and services, to leverage more scalable and trustable IoT platforms. Our proposed solution aims to provide an architecture that contributes to a more appropriate design for secure and reliable IoT systems. In this trend we propose a better use of edge-based support for local-enabled processing environments supporting IoT devices and users’ interactions, with operations intermediated by proximity hubs acting as gateways to the Blockchain, where the operations are regulated and controlled by verifiable smart-contracts involving data and transactions.